Multifunctionalization of Indoles: Synthesis of 3-Iodo-2-sulfonyl Indoles - Park, Hyowon; Bae, Junryeol; Son, Soobin; Jang, Hye Young (Bulletin of the Korean Chemical Society, 2019)
The selective multifunctionalization of indoles by using thiosulfonates, trimethyl sulfoxonium iodide (Me3SOI), and H2O2 was studied. The reaction of thiosulfonates with Me3SOI and H2O2 produced sulfonyl radicals and an iodination reagent, both of which were incorporated in indoles to form 3-iodo-2-sulfonyl indoles under carefully controlled conditions. The related reaction mechanism and the substrate scope of 3-iodo-2-sulfonyl indoles are presented.
Keywords: Indole; Iodination; Multi-functionalization; Sulfonylation; Thiosulfonate; Indole; Iodination; Multifunctionalization; Sulfonylation; Thiosulfonate